The roles and patterns of critical care pharmacists: a literature review and practical operation model in China - Wei, Chunyan; He, Jinhan; Zhang, Jingyi; Shan, Huifang; Jiang, Aidou; Liu, Ying; Chen, Guanghui; Xu, Chaoran; Wang, Linchao; Shao, Xiaofen; Yin, Wanhong (Frontiers in Pharmacology, 2024)
Drug-related problems (DRPs) are prevalent in critically ill patients and may significantly increase mortality risks. The participation of critical care pharmacists (CCPs) in the medical team has demonstrated a benefit to healthcare quality. Research indicates that CCP medication order evaluations can reduce DRPs, while their participation in rounds can reduce adverse drug events and shorten hospital stays. Pharmacist medication reconciliation often proves more effective than physicians, and CCPs play a crucial role in antimicrobial management and reducing treatment costs. Despite these benefits, there is a noticeable lack of practical guidance for implementing CCP roles effectively. Their workflow heavily influences the efficiency of CCPs. Integrating results from the literature with our practical experience, we have detailed workflows and critical entry points that CCPs can refer to. Pharmacists should be proactive rather than passive consultants. Pre-round medication order evaluations are crucial for determining the depth of a pharmacist's involvement in patient care. These evaluations should cover the following aspects: medication indication, dosage, treatment duration, detection of DRPs, implementation of therapeutic drug monitoring, dosing of sedatives and analgesics, and pharmaceutical cost containment. Beyond identifying medication issues, a primary task during rounds is gathering additional information and building trust with the medical team. Post-round responsibilities for CCPs include patient and caregiver education on medication, medication reconciliation for transitioning patients, and follow-up care for post-ICU patients. Establishing a rationalized and standardized workflow is essential to minimize daily work omissions and maximize the pharmacist's value. A multidisciplinary pharmacist-led team can significantly promote the rational use of antibiotics. Participation in post-ICU outpatient follow-ups can reduce drug-induced injuries after discharge. This review provides a detailed overview of the tasks performed by CCPs before, during, and after medical rounds, serving as a valuable reference for establishing an efficient workflow for CCPs.